When American Values Unite Jews and Muslim in the United States - Kasiyarno Kasiyarno (Universitas Ahmad Dahlan, 2022)
America was a big reputation as a melt pot for many nations with various backgrounds to live together since it could unite its people as one nation, including different religious groups or races. American Jews and Muslims belong to an American society that has co-existed for centuries. The twin towers collapse on September 11, 2011 has opened a very intensive dialog space between Muslim scholars and non-Muslims in America. In that situation, various scholarly Muslim forms of appreciation arise slowly towards other religious communities or the Jews. The commonalities between Jews and Muslims contribute significantly in making harmony among their followers. However, this paper insists that American values were the main factor in uniting Jews and Muslims in the United States